“I wish someone else could notify the partner”: barriers to STI partner notification identified and experienced by young women and health care workers in Cape Town, South Africa - Bennin, Fiona; Sindelo, Siyaxolisa; Mahlalela, Nomsa B.; Buttenheim, Alison; Egbe, Teniola; Vundhla, Prisca; Fuzile, Pamela; Jonas, Mbali; Mistri, Preethi; Maughan-Brown, Brendan; Rousseau, Elzette (Frontiers in Reproductive Health, 2025)
BackgroundSouth African clinical guidelines for sexually transmitted infections (STI) treatment and management recommend that all individuals who test positive should receive a notification slip to pass on to their partners. Despite these guidelines, partner notification and treatment rates remain low. Barriers include misinformation, gendered beliefs, and interpersonal concerns such as fear of stigma, violence, and being blamed for infidelity.Material and methodsWe used a behavioural design approach to explore challenges experienced by adolescent girls and young women (AGYW) in notifying their predominantly asymptomatic male partners about an STI diagnosis. A total of 7 AGYW and 8 Health Care Workers (HCWs) participated in behavioural mapping and co-design workshops in Cape Town, South Africa. Insights and solutions for partner notification were identified using the behavioural science NUDGE theory framework.ResultsParticipants experienced various emotions when receiving a positive STI result, including denial, confusion around mode of transmission, fear of the impact on their future, as well as anxiety around their partners’ reaction. HCWs noted AGYW's limited understanding of STIs and challenges in communicating the diagnosis to their partners, particularly when one or both partners were asymptomatic. Both groups criticized the current partner notification slip as overly complex and legalistic. Suggestions included simplified slips, and approaches that minimize AGYW's role in partner notification.ConclusionsOur results provide insight into the barriers experienced and identified by AGYW and HCWs, from AGYW receiving a positive STI test result, through notifying their partners. Next steps involve developing and testing high-fidelity prototypes that reduce the burden on AGYW and are feasible for integration into standard clinical care.